1986
DOI: 10.1111/j.1476-5381.1986.tb10211.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of the verapamil analogues, anipamil and ronipamil, against ischaemia‐induced arrhythmias in conscious rats

Abstract: Two analogues of verapamil, ronipamil and anipamil, were tested for their ability to reduce arrhythmias induced by occlusion of the left anterior descending coronary artery in conscious rats. Only anipamil (50 and 150 mg kg−1 orally) produced a statistically significant reduction in arrhythmias; it was most effective against ventricular fibrillation. Ronipamil at the same doses had limited antiarrhythmic actions. Only anipamil delayed the development of ECG signs of ischaemia, while both drugs reduced the magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 9 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…Nifedipine did, however, delay the process of isch-aemia and infarction, as indicated by a delay in the development of pathognomic ECG signs. This pattern of response is almost exactly the same as the pattern described previously for other calcium antagonists in the conscious rat (Curtis et al, 1984;1985a;1986b;Curtis & Walker, 1986) and is not related to antiarrhythmic activity. No class of drug has been consistently found to reduce infarct size in rats with permanent coronary occlusion; we have argued that this is expected , given the paucity of collateral anastamoses in rat ventricles.…”
Section: Infarct Sizesupporting
confidence: 87%
See 2 more Smart Citations
“…Nifedipine did, however, delay the process of isch-aemia and infarction, as indicated by a delay in the development of pathognomic ECG signs. This pattern of response is almost exactly the same as the pattern described previously for other calcium antagonists in the conscious rat (Curtis et al, 1984;1985a;1986b;Curtis & Walker, 1986) and is not related to antiarrhythmic activity. No class of drug has been consistently found to reduce infarct size in rats with permanent coronary occlusion; we have argued that this is expected , given the paucity of collateral anastamoses in rat ventricles.…”
Section: Infarct Sizesupporting
confidence: 87%
“…In previous studies we suggested that the antiarrhythmic effects of calcium antagonists occur entirely as a result of inhibition of Isi (Curtis et al, 1984;1985a;1986b;Curtis & Walker, 1986;Au et 8 1 '0 al., 1987), and that the site of action is most probably the ischaemic tissue. However, there appeared to be differences between the major classes of calcium antagonists, since we found that felodipine, a 1,4-dihydropyridine, had negligibile antiarrhythmic activity (Curtis et al, 1985a), whereas verapamil and other phenethylalkylamines (Curtis et al, 1984; I h 1986b; Curtis & Walker, 1986;Au et al, 1987) were effective, yet both classes of drugs produced similar reductions in blood pressure.…”
Section: Discussion Antiarrhythmic Activity Ofcalcium Antagonists In mentioning
confidence: 97%
See 1 more Smart Citation
“…Anipamil had a stronger antiarrhythmic than hypotensive effect compared to verapamil in rats [280]. Anipamil pretreatment proved to be protective against LAD ligation induced functional (monitored by ECG signs) and biochemical (creatine kinase loss) damage in rats.…”
Section: Anipamil Animal Studies With Anipamilmentioning
confidence: 86%
“…There are several animal studies showing the antiarrhythmic action of anipamil in rats [280]- [282] and also in pigs [283]. Anipamil had a stronger antiarrhythmic than hypotensive effect compared to verapamil in rats [280].…”
Section: Anipamil Animal Studies With Anipamilmentioning
confidence: 99%